Hurdles to uptake of mesenchymal stem cells and their progenitors in therapeutic products. Issue 17 (17th September 2020) - Childs, Peter G.; Reid, Stuart; Salmeron-Sanchez, Manuel; Dalby, Matthew J.
Abstract : Twenty-five years have passed since the first clinical trial utilising mesenchymal stomal/stem cells (MSCs) in 1995. In this time academic research has grown our understanding of MSC biochemistry and our ability to manipulate these cells in vitro using chemical, biomaterial, and mechanical methods . Research has been emboldened by the promise that MSCs can treat illness and repair damaged tissues through their capacity for immunomodulation and differentiation. Since 1995, 31 therapeutic products containing MSCs and/or progenitors have reached the market with the level of in vitro manipulation varying significantly. In this review, we summarise existing therapeutic products containing MSCs or mesenchymal progenitor cells and examine the challenges faced when developing new therapeutic products. Successful progression to clinical trial, and ultimately market, requires a thorough understanding of these hurdles at the earliest stages of in vitro pre-clinical development. It is beneficial to understand the health economic benefit for a new product and the reimbursement potential within various healthcare systems. Pre-clinical studies should be selected to demonstrate efficacy and safety for the specific clinical indication in humans, to avoid duplication of effort and minimise animal usage. Early consideration should also be given to manufacturing: how cell manipulation methods will integrate into highly controlled workflows and how they will be scaled up to produce clinically relevant quantities of cells. Finally, we summarise the main regulatory pathways for these clinical products, which can help shape early therapeutic design and testing.